Basics of Janus kinases: a review - Hanan R Nada; Maha F Elmasry; Dina A El Sharkawy; Sally Mamdouh (Wolters Kluwer Medknow Publications, 2020)
Janus kinases (JAKs) are a group of nonreceptor intracellular tyrosine kinases that could modify cytokine-mediated signals through the JAK-signal transducer and activator of transcription (STAT) pathway. The intracellular signaling pathway JAK/STAT has a principal role in sequential transfer of extracellular signals from cell membrane to the nucleus. This pathway is triggered by cytokines participating in inflammatory process, innate and adaptive immunological responses, as well as cell growth. Current researches suggest possible disruption in JAK/STAT pathway in different autoimmune and inflammatory skin diseases.